Afghanistan - Managing Public Finance for Development : Volume 2, Improving Public Financial Management - World Bank (Washington, DC, 2012)
Afghanistan's reconstruction has made considerable progress during the past four years. Led by the Government with international support but relying mostly on the energy and initiative of the Afghan people, reconstruction has resulted in solid achievements -- rapid economic growth, unprecedented primary school enrollments including enrollments for girls, great expansion of immunization, rehabilitation of major highways, a new and stable currency, promulgation of a new Constitution, Presidential and Parliamentary elections, return of refugees, and demobilization of militias. Public finance management has made a major contribution to these successes. Yet the challenges remain enormous. The main objective of this Afghanistan Public Finance Management Review is to consolidate, deepen, and present in an accessible, action-oriented form the knowledge base on Afghanistan's public finance system, review recent progress, analyze key challenges, and put forward options and recommendations for moving forward. This main report is supplemented by four additional volumes, covering public finance management performance and procurement (Volume 2); key cross-cutting issues (Volume 3); selected sector studies (Volume 4); and security sector expenditures (Volume 5).